Energy Losses and Effects of Renewable and Non-Renewable Energy Use on Energy Intensity: An Analysis on Malaysia Using Fourier Models - Özbek, Bahar (International Journal of Contemporary Economics and Administrative Sciences, 2025)
With the globalization process, interactions between developed and developing economies are increasing. With these interactions, the search for common solutions to global problems is increasing. Among the most important global problems are climate change and global warming. Carbon dioxide emissions are among the main determinants of this problem. There are many suggestions on a global scale to reduce carbon dioxide emissions. The environmental dimension is of great importance among the Sustainable Development goals set by the United Nations. The environmental dimension also includes the production and consumption of energy resources. This situation makes energy resources important on a global scale. This study investigates the determinants of energy intensity in the Malaysian economy, which is among the developing countries. In this context, renewable energy, non-renewable energy use, energy losses and energy density variables for the 1990-2020 sample period are used. The Fourier methodology is used as an empirical method in the study. The existence of a long-term relationship between the variables in the empirical model is reached. Empirical results have shown that non-renewable energy use and energy resources increase energy intensity. On the other hand, it has been concluded that the use of renewable energy, known as a clean energy source, is a factor that reduces energy intensity.